The Influence of Accounting Understanding, Use of Accounting Information Systems and Educational Level on the Quality of Village Government Financial Reporting Information in Kundur District - Praptiningsih; Mashuri, Ayunita Ajengtiyas Saputri; Fitri Yetty (Yayasan Sinergi Kawula Muda, 2023)
The purpose of this study was to determine whether understanding of accounting, utilization of accounting information systems and educational level affect the quality of financial reporting information. This research was conducted in village government in Kundur District, namely Sungai Ungar Village, Sungai Sebesi Village and Lubuk Village. This type of research is quantitative, by distributing questionnaires to village officials as many as 62 respondents. All village apparatus in Kundur subdistrict, totaling 62 village apparatus. Data analysis in this study used descriptive statistical analysis, data quality test, classical assumption test, multiple linear regression analysis and hypothesis testing was carried out using IBM SPSS 26 and Microsoft Excel 2010. The results of this study shows that the accounting understanding variable has a positive effect on the quality of financial reporting information, the accounting information system utilization variable has a positive effect on the quality of financial reporting information and the education level variable has a positive effect on the quality of financial reporting information.